Ecological Vulnerability Assessment Integrating the Spatial Analysis Technology with Algorithms: A Case of the Wood-Grass Ecotone of Northeast China - Zhi Qiao; Xi Yang; Jun Liu; Xinliang Xu (Abstract and Applied Analysis)
This study evaluates ecological vulnerability of the wood-grass ecotone of northeast China integrating the spatial analysis technology with algorithms. An assessment model of ecological vulnerability is developed applying the Analytical Hierarchy Process. The composite evaluation index system is established on the basis of the analysis of contemporary status and potential problems in the study area. By the application of the evaluation model, ecological vulnerability index is calculated between 1990 and 2005. The results show that ecological vulnerability was mostly at a medium level in the study area, however the ecological quality was deteriorating. Through the standard deviational ellipse, the variation of ecological vulnerability can be spatially explicated. It is extremely significative for the prediction of the regions that will easily deteriorate. The deterioration zone was concentrating in the area of Da Hinggan Ling Mountain, including Xingan League, Chifeng, Tongliao, and Chengde, whereas the improvement zone was distributing in the north-central of Hulunbeier.